The Influence of Environmental Sanitation on Incidence of Stunting: A Systematic Review - Cahyawati, Sunik; Riana, Eka (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2025)
Background: Stunting is a chronic health problem that has long-term impacts on child growth and development, especially in developing countries. Poor environmental sanitation is believed to be one of the main risk factors; however, this needs to be further examined based on empirical study findings. This study aims to analyze this issue systematically. Subjects and Method: This is a systematic review using the PRISMA Flow Diagram. The PICO framework includes: Population (P): Children under five years of age; Intervention (I): Poor environmental sanitation; Comparison (C): Adequate environmental sanitation; Outcome (O): Stunting. Articles were retrieved from databases including PubMed, Scopus, ScienceDirect, and Google Scholar. Keywords used were “hygiene AND sanitation AND stunting AND under five AND cross-sectional.” The quality of the studies was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal tool. Results: A total of 9 articles from four studies were conducted in Asia, all of which from Indonesia, and five studies were conducted in Africa, all of which from the Ethiopia, indicated that access to proper sanitation, clean water, as well as appropriate feces disposal and handwashing practices, are strongly associated with a reduction in stunting incidence. The risk of stunting increases among children living in environments with unimproved latrines, untreated drinking water, and poor hygiene practices. Additional factors such as the child’s age, mother’s education level, and socioeconomic status also influence stunting outcomes. Conclusion: Inadequate environmental sanitation plays a significant role in the occurrence of stunting. Preventive interventions should prioritize improving sanitation access, promoting hygiene behavior education, and implementing cross-sectoral approaches to sustainably reduce stunting prevalence.